A colónia Baba, 1932-1936; 2014. 3 exemplos de ruptura e/ou continuidade do dispositivo doméstico - André de Brito Malveiro (2014)
The following thesis has as a main topic the Baba Housing State, built in Prague between 1932 and 1936. This Housing State was the latest in a series of exhibitions held by the instituion Werkbund. Its houses have the particularity of having been designed by different architects, advised by its future users, whohave imposed their wills on individual projects.During the investigation were selected three different houses of this Housing State. We seek assess the changes that these houses suffered when compared its original state (1932) to its current state (2014). We question whether there is a break or a continuity in relation to its original domestic space and what is the most practicable path to follow according to houses' rehab: intervene based on a return to the origins of the original project or intervene absorbing the appropriations of their owners? These are the issues to aim. These are the slogans we have established.In other words, the study of the house: the projected one and the lived one.